Latihan fisik teratur memiliki efek positif dalam meningkatkan kapasitas aerobik pada siswa militer. - Pranata Aji Kusuma; Slamet Riyadi; Selfi Handayani (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Military preparation requires aerobic capacity (VO2max) and physical condition. Studies show that Indonesian Air Force personnel are overweight (34.9%) and obese (9.1%), which may impede task performance. This study examines how stair ascending and descending improve aerobic capacity (VO2 max) in Skadron Pendidikan 404 (Skadik 404) cadets, with BMI as a supportive factor. A quasi-experimental study included 40 cadets aged 19-22 with a BMI of 18.5-24.9 kg/m², divided into four groups: POK 1 (stair climbing), POK 2 (stair descending), POK 3 (stair climbing), and POK 4 (stair descending). This study uses 'POK' to refer to each study group. Data was collected using the 12-minute Cooper Test to measure VO2max. The data was analyzed using pairwise t-tests and two-way ANOVA with 5% significance. The study found significant differences in aerobic capacity (p < 0.05), with the stair-climbing group achieving larger VO₂max improvements than the descending group. These results show that army students may benefit more from stair climbing for aerobic training. This study supports military fitness studies by showing that stair climbing is better than stair descending and suggesting time-efficient, high-intensity training routines to improve soldiers' physical readiness.